Öffentlich Grenzen überschreiten: Notfallseelsorge als Herausforderung für Praxis und kirchenleitendes Handeln - Rinn, Angela (Pastoraltheologie, 2016)
Crossing Frontiers Publicly : Emergency Spiritual Care as a Challenge for the Practice and for the Responsibilities of Church Leadership. Since the 1990s emergency spiritual care administered on-site by an ecumenical on-call service has been developed in Germany for cases of major traffic accidents or other disasters with a larger number of casualties. The service is provided by the majority Protestant Church and the Catholic Church. It has also extended its work to offering support to emergency helpers to care for the helpers, to breaking the news of sudden death or a suicide to close relatives, and to supporting relatives after a sudden death at home while medical personnel and police investigators are doing their job. This church involvement started at the grass roots and is implemented by volunteer counselors (mostly pastors), in some regions by volunteer pastors and in others expected from all the pastors. It has become highly cherished and expected by the public. However, with shrinking numbers of pastors it becomes questionable as to how it can be secured in the future. The author reflects on the ecclesiolocial status of this activity and also makes a suggestion about how churches might sucessfully regulate the matter.